Preparation method of efficient and safe ultrathin copper current collector for negative electrode of lithium metal battery
By forming a nano-scale porous structure on the surface of the copper foil and compounding it with lithium, the problems of lithium dendrites growth and unstable battery performance in lithium metal batteries are solved, and efficient and safe preparation of ultra-thin copper current collectors for lithium metal batteries are achieved. Improves the cycle stability and energy density of the battery.
Patent Information
- Application Number
- CN202411426101.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
AI Technical Summary
Lithium metal batteries face safety problems caused by low Coulomb efficiency, unstable circulation performance and uncontrolled growth of lithium dendrites. This is mainly due to the compatibility problems between oxygen-free copper and liquid lithium, which leads to physical dissolution and corrosion of copper, affecting the battery. energy density and service life.
Nano-scale porous structures are grown on the surface of the copper foil and combined with lithium. Ultra-thin copper current collectors are formed through heat treatment and chemical cleaning, which improves the uniform deposition and conductivity of lithium, inhibits the growth of lithium dendrites, and improves battery performance.
The nano-scale porous copper structure increases the transmission channel of lithium ions, alleviates the volume expansion caused by lithium metal deposition, improves the cycle stability and high-magnification capacity of the battery, significantly inhibits the growth of lithium dendrites, improves the uneven current distribution, and adapts to electrodes. The volume changes during charging and discharging improve the overall performance of the battery.
Smart Images

Figure CN119307847A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ultra-thin copper current collector preparation, and specifically relates to a method for preparing an efficient and safe ultra-thin copper current collector for a negative electrode of a lithium metal battery. Background Art
[0002] As a key commercial energy solution, lithium-ion batteries have been widely used in many fields, from electric toys to advanced smart devices. However, due to the theoretical specific capacity of graphite (372 mAhg -1 ) is too low to meet people's demand for energy, which has promoted the exploration of battery systems with higher energy density. Lithium metal has become one of the most promising candidate materials in the next generation of electrochemical energy storage systems due to its low electrochemical potential and high specific capacity. Despite this, lithium metal batteries face many challenges, including low Coulombic efficiency, unstable cycle performance, uncontrolled growth of lithium dendrites and the resulting safety issues. In the current field of lithium-ion battery technology, the preparation of metallic lithium and copper current collector composites is a core technology. Due to the serious compatibility issues between oxygen-free copper and liquid lithium, the corrosion of liquid lithium on oxygen-free copper is mainly manifested as physical dissolution of copper and corrosion of copper grain boundaries by liquid lithium.
[0003] In order to solve the above problems and scale up production, the research team is committed to developing a new type of nanoporous copper current collector. This current collector is designed to disperse the current density, promote the uniform nucleation and growth of lithium on the entire electrode, thereby effectively inhibiting the formation of lithium dendrites and preventing structural damage caused by the huge volume expansion of lithium. By improving the nucleation and growth environment of lithium metal, it can not only effectively inhibit the growth of dendrites, but also optimize the energy density and service life of the battery, further promoting the development of lithium metal battery technology. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing an efficient and safe ultra-thin copper current collector for a lithium metal battery negative electrode, which grows a nano-scale porous structure on the surface of the copper foil and uses it to composite lithium, thereby achieving uniform deposition of lithium metal and inhibiting the growth of lithium dendrites. The specific steps are as follows: 1) Use ethanol solution to remove stains on the surface of the brass foil, then immerse it in ammonium chloride solution to remove the copper oxide layer on the surface, then wash the brass foil with deionized water to remove the residual solution and impurities on the surface of the brass foil, and finally place the cleaned brass foil in a vacuum drying oven to dry at a constant temperature; 2) Cover the dried brass foil with two layers of titanium mesh to ensure that the copper foil is not wrinkled after heat treatment, and then put it into a vacuum atmosphere furnace, start the vacuum pump to exhaust the air in the vacuum atmosphere furnace, and then connect the inert gas to keep the inert gas atmosphere in the vacuum atmosphere furnace to prevent oxidation during the heat treatment process. Heat the vacuum atmosphere furnace to 600-1000℃ for insulation, and then cool it to 300-400℃ with the furnace, then take out the copper foil and cool it to room temperature in the air to oxidize the copper foil in the air; 3) The oxidized copper foil is placed in an ammonium chloride solution for cleaning to remove copper oxide and impurities on the surface of the copper foil, thereby obtaining a porous copper foil having a nanopore structure on the surface. The porous copper foil is then cleaned in anhydrous ethanol to remove residual solution and impurities, and finally dried in a vacuum drying oven at a constant temperature and taken out. 4) The dried porous copper foil is heated on a heating platform in a glove box filled with argon gas, and is removed after being in contact with molten lithium metal. It is then taken out after being cooled to room temperature to obtain an ultra-thin copper current collector.
[0005] Preferably, in the step 1), the mass ratio of copper to zinc in the brass foil is 65-70:30-35, and the thickness is 5 μm-1 mm.
[0006] Preferably, the concentration of ammonium chloride in step 1) is 0.1-5 mol / L, and the immersion time is 1-60 s.
[0007] Preferably, in step 1), the constant temperature drying temperature is 60-100° C., and the drying time is 4-6 hours.
[0008] Preferably, in step 2), the heating rate of the vacuum atmosphere furnace is 1-50° C. / min, and the holding time is 10-30 min.
[0009] Preferably, the inert gas in step 2) is argon.
[0010] Preferably, in step 3), the drying temperature is 20-100° C. and the drying time is 0-12 h.
[0011] Preferably, in step 3), the concentration of ammonium chloride is 0.1-5 mol / L, the washing time of ammonium chloride is 1-60 s, and the washing time of anhydrous ethanol is 1-60 s.
[0012] Preferably, in step 4), the heating platform is heated to 300-350° C., the temperature of the metal lithium is 300-350° C., and the contact time is 2-5 s.
[0013] Compared with the prior art, the present invention has the following advantages: The present invention performs air cooling treatment on the copper foil in oxygen or air to grow a uniform and thin layer of CuO on its surface. After removing the surface CuO and impurities, a porous copper foil containing nano-scale holes is left. These holes are independent and evenly distributed, with small pore size and high uniformity, and have good conductivity and heat resistance. This structure not only increases the transmission channel of lithium ions and reduces the local aggregation of lithium ions on the electrode surface, but also effectively alleviates the volume expansion problem caused by lithium metal deposition and maintains the stability of battery performance. This structure further alleviates the lithium metal negative electrode by accommodating the deposited metal lithium. Volume effect. The introduction of this structure can not only adapt to the volume change of the electrode during the charging and discharging process, but also provide an optimized path for the rapid transmission of lithium ions, thereby improving the cycle stability and high-rate capacity of the battery. At the same time, the porous copper foil is heated at high temperature and compounded with lithium to form a layer of lithium-copper alloy. This step can not only significantly improve the affinity of lithium metal, which is beneficial to the uniform deposition of lithium metal, but also significantly inhibit the growth of lithium dendrites, and can effectively improve the uneven current distribution of the lithium metal negative electrode. The preparation process of the method of the present invention is simple and controllable, with low energy consumption, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is a SEM image of the ultra-thin copper current collector prepared in Example 1 of the present invention; Figure 2 is a SEM image of the ultra-thin copper current collector prepared in Example 2 of the present invention; Figure 3 is a SEM image of the ultra-thin copper current collector prepared in Example 3 of the present invention; Figure 4 is a SEM image of the ultra-thin copper current collector prepared in Comparative Example 1 of the present invention; Figure 5 is a SEM image of the ultra-thin copper current collector prepared in Comparative Example 4 of the present invention; Figure 6 This is a comparison chart of the half-cell cycle performance assembled using the ultra-thin copper current collectors prepared in Example 1 and Comparative Example 1; Figure 7 This is a comparison chart of the cycle performance of symmetrical batteries assembled using the ultra-thin copper current collectors prepared in Example 1 and Comparative Example 1; Figure 8 This is a comparison chart of the cycle performance of full batteries assembled using the ultra-thin copper current collectors prepared in Example 1 and Comparative Example 1; Fig. 9 It is a comparison chart of the rate cycling performance of full batteries assembled using the ultra-thin copper current collectors prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0015] The technical solution of the present invention is clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] The present invention proposes a highly efficient and safe method for preparing an ultra-thin copper current collector for a lithium metal battery negative electrode, which grows a nano-scale porous structure on the surface of a copper foil and uses it to composite lithium, thereby achieving uniform deposition of lithium metal and inhibiting the growth of lithium dendrites. The specific steps are as follows: 1) Use ethanol solution to remove stains on the surface of the brass foil, then immerse it in ammonium chloride solution to remove the copper oxide layer on the surface, then wash the brass foil with deionized water to remove the residual solution and impurities on the surface of the brass foil, and finally place the cleaned brass foil in a vacuum drying oven to dry at a constant temperature; 2) Cover the dried brass foil with two layers of titanium mesh to ensure that the copper foil is not wrinkled after heat treatment, and then put it into a vacuum atmosphere furnace, start the vacuum pump to exhaust the air in the vacuum atmosphere furnace, and then connect the inert gas to keep the inert gas atmosphere in the vacuum atmosphere furnace to prevent oxidation during the heat treatment process. Heat the vacuum atmosphere furnace to 600-1000℃ for insulation, and then cool it to 300-400℃ with the furnace, then take out the copper foil and cool it to room temperature in the air to oxidize the copper foil in the air; 3) The oxidized copper foil is placed in an ammonium chloride solution for cleaning to remove copper oxide and impurities on the surface of the copper foil, thereby obtaining a porous copper foil having a nanopore structure on the surface. The porous copper foil is then cleaned in anhydrous ethanol to remove residual solution and impurities, and finally dried in a vacuum drying oven at a constant temperature and taken out. 4) The dried porous copper foil is heated on a heating platform in a glove box filled with argon gas, and is removed after being in contact with molten lithium metal. It is then taken out after being cooled to room temperature to obtain an ultra-thin copper current collector.
[0017] Wherein, in step 1), the mass ratio of copper to zinc in the brass foil is 65-70:30-35, the thickness is 5 μm-1 mm, the concentration of ammonium chloride is 0.1-5 mol / L, the immersion time is 1-60 s, the constant temperature drying temperature is 60-100° C., and the drying time is 4-6 h.
[0018] Wherein, in step 2), the heating rate of the vacuum atmosphere furnace is 1-50°C / min, the insulation time is 10-30min, and the inert gas is argon.
[0019] Wherein, in step 3), the drying temperature is 20-100° C., the drying time is 0-12 h, the concentration of ammonium chloride is 0.1-5 mol / L, the ammonium chloride cleaning time is 1-60 s, and the anhydrous ethanol cleaning time is 1-60 s.
[0020] Wherein, in step 4), the heating platform is heated to 300-350°C, the temperature of the metal lithium is 300-350°C, and the contact time is 2-5s. Example
[0021] 1) Remove the surface stains of 10μm thick H68 brass foil with ethanol solution, then immerse it in 1mol / L ammonium chloride solution for 30s to remove the surface copper oxide layer, and then remove the residual solution and impurities on the surface of the copper foil with deionized water. Finally, place the cleaned H68 brass foil in a vacuum drying oven at 80℃ for 6 hours for use; 2) Cover the dried H68 brass foil with two layers of titanium mesh to ensure that the copper foil is not wrinkled after heat treatment, put it into a vacuum atmosphere furnace, start the vacuum pump to remove the air in the vacuum atmosphere furnace, and then connect Ar gas to maintain an inert gas atmosphere in the vacuum atmosphere furnace to prevent oxidation of the sample during heat treatment. Heat the vacuum atmosphere furnace to 600℃ at a heating rate of 30℃ / min and keep it warm for 30min. Cool it to 300℃ in the furnace, then take it out and cool it to room temperature in the air to oxidize the copper foil in the air; 3) The oxidized copper foil was placed in a 1 mol / L ammonium chloride solution and washed for 30 seconds to remove the surface copper oxide and impurities, thereby obtaining a porous copper foil with a nanopore structure on the surface. The foil was then washed in anhydrous ethanol for 15 seconds to remove the residual solution and impurities. The foil was finally dried in a vacuum drying oven at 80°C for 6 hours. 4) The treated porous copper foil is heated to 300°C using a heating platform in a glove box filled with argon gas, and is placed in contact with molten lithium at 300°C for 3 seconds before being removed. The foil is then cooled to room temperature and taken out to obtain an ultra-thin copper current collector. Example
[0022] 1) Immerse 5um thick H68 brass foil in 0.5mol / L ammonium chloride solution for 60s to remove the surface copper oxide layer, then use deionized water to remove the residual solution and impurities on the surface of the copper foil, and finally place the cleaned H68 brass foil in a vacuum drying oven at 90℃ for 4 hours for use; 2) Cover the dried H68 brass foil with two layers of titanium mesh to ensure that the copper foil is not wrinkled after heat treatment, put it into a vacuum atmosphere furnace, start the vacuum pump to remove the air in the vacuum atmosphere furnace, and then connect Ar gas to maintain an inert gas atmosphere in the vacuum atmosphere furnace to prevent oxidation of the sample during heat treatment. Heat the vacuum atmosphere furnace to 700℃ at a heating rate of 15℃ / min and keep it warm for 20min. Cool it to 350℃ with the furnace, then take it out and cool it to room temperature in the air to oxidize the copper foil in the air; 3) First, the oxidized copper foil was placed in a 0.5 mol / L ammonium chloride solution for 30 seconds to remove the surface copper oxide and impurities, and a porous copper foil with a nanopore structure on the surface was obtained. Then, the copper foil was washed in anhydrous ethanol for 15 seconds to remove the residual solution and impurities, and finally, the copper foil was dried at a constant temperature of 90°C for 4 hours in a vacuum drying oven. 4) The treated porous copper foil is heated to 350°C using a heating platform in a glove box filled with argon gas, and is brought into contact with molten lithium metal at 350°C for 2 seconds before being removed. The foil is then cooled to room temperature and taken out to obtain an ultrathin copper current collector. Example
[0023] 1) Immerse 20μm H68 brass foil in 2mol / L ammonium chloride solution for 15s to remove the copper oxide layer on the surface, then use deionized water to remove the residual solution and impurities on the surface of the copper foil, and finally place the cleaned H68 brass foil in a vacuum drying oven at 60℃ for 6 hours for later use; 2) Cover the dried H68 brass foil with two layers of titanium mesh (to ensure that the copper foil is not wrinkled after heat treatment) and put it into a vacuum atmosphere furnace. Start the vacuum pump to remove the air in the vacuum atmosphere furnace, and then connect Ar gas to maintain an inert gas atmosphere in the vacuum atmosphere furnace to prevent the sample from oxidizing during the heat treatment process. Heat the vacuum atmosphere furnace to 800℃ at a heating rate of 5℃ / min and keep it warm for 10min. Cool it to 400℃ with the furnace, then take it out and cool it to room temperature in the air to oxidize the copper foil in the air; 3) The oxidized copper foil was placed in a 2 mol / L ammonium chloride solution and washed for 15 seconds to remove the surface copper oxide and impurities, thereby obtaining a porous copper foil with a nanopore structure on the surface; then, the foil was washed in anhydrous ethanol for 15 seconds to remove the residual solution and impurities; finally, the foil was dried in a vacuum drying oven at 60°C for 6 hours and then taken out; 4) The treated porous copper foil is heated to 400°C using a heating platform in a glove box filled with argon gas, and is placed in contact with molten lithium at 400°C for 1 second before being removed. The foil is then cooled to room temperature and taken out to obtain an ultra-thin copper current collector.
[0024] Comparative Example 1 Step 2) continuously heating to 500° C. at a heating rate of 30° C. / min in a vacuum atmosphere furnace and keeping the temperature for 3 h. The rest is the same as in Example 1.
[0025] Comparative Example 2 Step 2) continuously heating to 800° C. at a heating rate of 30° C. / min in a vacuum atmosphere furnace and keeping the temperature for 3 h. The rest is the same as in Example 1.
[0026] Comparative Example 3 In step 4), the copper foil is not heated but is brought into contact with the molten metallic lithium. The remaining steps are the same as those in Example 1.
[0027] Comparative Example 4 In step 3), no ammonium chloride solution and anhydrous ethanol are used for cleaning, and the remaining steps are the same as those in Example 1.
[0028] Comparative Example 5 In step 4), the contact time between the copper foil and the metallic lithium is 30 seconds, and the remaining steps are the same as those in Example 1.
[0029] Comparative Example 6 In step 2), the product is taken out directly without being cooled in the furnace, and the remaining steps are the same as those in Example 1.
[0030] The ultra-thin copper current collectors prepared in Examples 1-3 and Comparative Examples 1-6 were tested, and the results are shown in Table 1 below: Table 1
[0031] Figure 1-5 3D porous copper current collectors prepared in Examples 1-3 and Comparative Examples 1 and 4 of the present invention are SEM images. It can be seen from the images that Examples 1-3 all have nano-scale porous copper, while Comparative Examples 1 and 4 do not.
[0032] Mechanism: In the manufacturing process of porous copper foil, precise control of furnace cooling temperature is crucial for the preparation of porous copper foil. Annealing is a heat treatment process that can change the physical and chemical properties of metals. Through annealing, various structural defects and residual stresses generated in the preparation process of porous copper foil can be improved or eliminated, so that the three-dimensional porous copper foil can avoid deformation or collapse of the three-dimensional structure caused by stress concentration and cracks caused by rapid cooling, which helps to reduce lattice defects and improve the orderliness of crystals, thereby improving its conductivity and mechanical properties.
[0033] The ultra-thin copper current collectors prepared in Example 1 and Comparative Example 1 were assembled into half-cells, symmetrical cells and full cells with lithium iron phosphate as the positive electrode for constant current charge and discharge tests. The results are shown in the attached figure. Figure 6-9As shown, the ultra-thin copper current collector prepared in Example 1 is assembled into a half-cell, a symmetrical cell, and a full cell with lithium iron phosphate as the positive electrode sheet. The cycle performance is better than that of Comparative Example 1. This is because by constructing a three-dimensional current collector / lithium metal composite negative electrode, the deposition behavior of lithium can be effectively improved, and the growth of lithium dendrites can be inhibited to a certain extent, thereby significantly improving the coulombic efficiency, cycle life and rate performance of the battery. This improvement is due to the introduction of a three-dimensional porous structure, which not only increases the transmission channel of lithium ions, reduces the local aggregation of lithium ions on the electrode surface, but also effectively alleviates the volume expansion problem caused by lithium metal deposition, and maintains the stability of battery performance. The three-dimensional porous current collector structure further alleviates the volume effect of the lithium metal negative electrode by accommodating the deposited metallic lithium. The introduction of this structure can not only adapt to the volume change of the electrode during the charge and discharge process, but also provides an optimized path for the rapid transmission of lithium ions, thereby improving the cycle stability and high rate capacity of the battery. By integrating the lithium foil and the copper current collector, a Li / Cu current collector negative electrode with a three-dimensional structure is prepared, which effectively improves the unevenness of the current distribution of the lithium metal negative electrode.
[0034] The above descriptions are merely embodiments of the present invention. It should be pointed out that, for those skilled in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the technical principles of the present invention. These changes, modifications, substitutions and variations should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an efficient and safe ultra-thin copper current collector for a lithium metal battery negative electrode, characterized in that: The specific steps are as follows: 1) Use ethanol solution to remove stains on the surface of the brass foil, then immerse it in ammonium chloride solution to remove the copper oxide layer on the surface, then wash the brass foil with deionized water to remove the residual solution and impurities on the surface of the brass foil, and finally place the cleaned brass foil in a vacuum drying oven to dry at a constant temperature; 2) Cover the dried brass foil with two layers of titanium mesh to ensure that the copper foil is not wrinkled after heat treatment, and then put it into a vacuum atmosphere furnace, start the vacuum pump to exhaust the air in the vacuum atmosphere furnace, and then connect the inert gas to keep the inert gas atmosphere in the vacuum atmosphere furnace to prevent oxidation during the heat treatment process. Heat the vacuum atmosphere furnace to 600-1000℃ for insulation, and then cool it to 300-400℃ with the furnace, then take out the copper foil and cool it to room temperature in the air to oxidize the copper foil in the air; 3) The oxidized copper foil is placed in an ammonium chloride solution for cleaning to remove copper oxide and impurities on the surface of the copper foil, thereby obtaining a porous copper foil having a nanopore structure on the surface. The porous copper foil is then cleaned in anhydrous ethanol to remove residual solution and impurities, and finally dried in a vacuum drying oven at a constant temperature and taken out. 4) The dried porous copper foil is heated on a heating platform in a glove box filled with argon gas, and is removed after being in contact with molten lithium metal. It is then taken out after being cooled to room temperature to obtain an ultra-thin copper current collector.
2. The method for preparing an efficient and safe ultra-thin copper current collector for a negative electrode of a lithium metal battery according to claim 1, characterized in that: In the step 1), the mass ratio of copper to zinc in the brass foil is 65-70:30-35, and the thickness is 5 μm-1 mm.
3. The method for preparing an efficient and safe ultra-thin copper current collector for a negative electrode of a lithium metal battery according to claim 1, characterized in that: In step 1), the concentration of ammonium chloride is 0.1-5 mol / L, and the immersion time is 1-60 s.
4. The method for preparing an efficient and safe ultra-thin copper current collector for a negative electrode of a lithium metal battery according to claim 1, characterized in that: In the step 1), the constant temperature drying temperature is 60-100° C. and the drying time is 4-6 hours.
5. The method for preparing an efficient and safe ultra-thin copper current collector for a negative electrode of a lithium metal battery according to claim 1, characterized in that: In the step 2), the heating rate of the vacuum atmosphere furnace is 1-50° C. / min, and the holding time is 10-30 min.
6. The method for preparing an efficient and safe ultra-thin copper current collector for a negative electrode of a lithium metal battery according to claim 1, characterized in that: In step 2), the inert gas is argon.
7. The method for preparing an efficient and safe ultra-thin copper current collector for a negative electrode of a lithium metal battery according to claim 1, characterized in that: In step 3), the drying temperature is 20-100° C. and the drying time is 0-12 hours.
8. The method for preparing an efficient and safe ultra-thin copper current collector for a negative electrode of a lithium metal battery according to claim 1, characterized in that: In step 3), the concentration of ammonium chloride is 0.1-5 mol / L, the ammonium chloride cleaning time is 1-60 s, and the anhydrous ethanol cleaning time is 1-60 s.
9. The method for preparing an efficient and safe ultra-thin copper current collector for a negative electrode of a lithium metal battery according to claim 1, characterized in that: In the step 4), the heating platform is heated to 300-350° C., the temperature of the metal lithium is 300-350° C., and the contact time is 2-5 seconds.
Citation Information
Patent Citations
Three-dimensional porous copper oxide modified copper foil for lithium metal battery current collector as well as preparation method and application thereof
CN111600036A
Three-dimensional porous nano-copper current collector and preparation method thereof
CN117096349A
Lithium negative electrode material without dendritic crystal on surface, battery and preparation method
CN117525299A
Storage device and operating method thereof
KR1020210026895A
Process for treating high-density information disc recording substrates
US4469563A